A survey on indexing techniques for mobility in Internet of Things': Challenges, performances, and perspectives. Issue 4 (21st February 2020) - Badarneh, Hazem Jihad; Ravana, Sri Devi; Mansoor, Ali Mohammed
Summary: Mobile nodes arouse new challenges that expand the performance in those environments. The nodes of Internet of Things (IoT) generate a large amount of data, which have to be stored and processed in a seamless and interpretable form by indexing. Therefore, indexing is a challenge in IoT, particularly when the nodes are mobile. The current indexing techniques dedicated to mobile environments are unsatisfying because the data are transmitted from different locations within different time periods and randomness of sensor movement. Although huge research efforts have been dedicated to this subject amid the last decades, little consideration has been paid for the research summarization and guidance. The objective of this survey is to identify the relationship between activities of mobile sensors in the context of IoT, that concerned on transferring and collecting data as well as the effectiveness of indexing techniques. The contribution of this review is to investigate the techniques of mobile IoT nodes, to find the source of challenges that adversely affect the index effectiveness. In‐depth investigation and analyses of approaches to apply IoT mobile nodes will enable the researcher to understand the behavior of mobile environments to extract the deformities that adversely affect the indexing effectiveness. The analyzed approaches are meta‐heuristic, spatial‐temporal indexing, and prediction model approach. Each approach is analyzed by discussing the features and limitations from the mobility perspectives. Furthermore, the indexing techniques are analyzed according to their features and limitations and mobile IoT indexing requirements. In conclusion, recognize and contemplate different open issues that got little focus or still unknown at this point. Abstract : The objective of this review was finding the challenges of indexing techniques of mobile sensor nodes in IoT. This work studied the correlation between the mobile sensor techniques and indexing techniques, as well as highlighting the disadvantages and challenges in mobile sensor techniques from the indexing techniques perspective. This work finds that indexing data of mobile sensors in IoT requires an efficient indexing technique, which can handle mobile IoT data, to minimize indexing overhead.